2011
DOI: 10.1186/1751-0147-53-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of clinical manifestations, haematological and serological responses after experimental infection with Anaplasma phagocytophilum in two Norwegian sheep breeds

Abstract: BackgroundIt has been questioned if the old native Norwegian sheep breed, Old Norse Sheep (also called Norwegian Feral Sheep), normally distributed on coastal areas where ticks are abundant, is more protected against tick-borne infections than other Norwegian breeds due to a continuously high selection pressure on pasture. The aim of the present study was to test this hypothesis in an experimental infection study.MethodsFive-months-old lambs of two Norwegian sheep breeds, Norwegian White (NW) sheep and Old Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 21 publications
4
18
0
2
Order By: Relevance
“…However, morulae were not observed in the two clinical cases that were RLB positive for A. phagocytophilum. This finding is supported by a previous report of Anaplasma DNA detected as early as five days before inclusions were observed by blood smear microscopy (Stuen et al, 2011). We found parasitemia of 0.2-1.6% in animals, consistent with the view that the percent of infected leukocytes varies markedly .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, morulae were not observed in the two clinical cases that were RLB positive for A. phagocytophilum. This finding is supported by a previous report of Anaplasma DNA detected as early as five days before inclusions were observed by blood smear microscopy (Stuen et al, 2011). We found parasitemia of 0.2-1.6% in animals, consistent with the view that the percent of infected leukocytes varies markedly .…”
Section: Discussionsupporting
confidence: 94%
“…We found parasitemia of 0.2-1.6% in animals, consistent with the view that the percent of infected leukocytes varies markedly . In addition, a recent study found the infection rate to be significantly different on days 3, 6, 7, and 8 in experimentally infected sheep (Stuen et al, 2011). Therefore, molecular diagnostic tools represent a more sensitive method, and the time frame for detection of A. phagocytophilum is longer when using molecular methods than with thin blood smears Nieder et al, 2012).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Investigators of another study 26 in which a large sample of inoculum of A phagocytophilum was subdivided into small aliquots for the in-oculation of individual sheep (a procedure similar to that used in the study reported here) found that a few aliquots lacked a sufficient infective dose because of minor stochastic differences. All sheep in the present study received approximately the same dose of A phagocytophilum, but only a small proportion seroconverted or developed bacteremia.…”
Section: Discussionmentioning
confidence: 95%
“…Individual variation in response to A . phagocytophilum infection in sheep is evident and shown by Granquist et al [27] and Stuen et al [28]. Furthermore, genetic variation in lamb survival on tick exposed pastures has also been reported [29].…”
Section: Introductionmentioning
confidence: 99%